Higher Education Subsidies and the Universal Insurance against a Short Life - Gregory Ponthiere (Global Labor Organization (GLO), 2024)
This paper examines the potential role of higher education subsidies as an insurance device against the risk of having a short life, that is, as a device reducing the variance in lifetime well-being due to unequal longevities. We use a two-period dynamic OLG economy with human capital and risky lifetime to study the impact of a subsidy on higher education (financed by taxing labor earnings at older ages) on the distribution of lifetime well-being between long-lived and short-lived individuals. It is shown that, whereas the subsidy on higher education improves necessarily the lot of short-lived individuals in comparison to the laissez-faire, it is only when the subsidy is higher than a critical threshold that this reduces inequalities in lifetime well-being between long-lived and short-lived individuals. Whether one adopts the utilitarian or the ex post egalitarian social welfare function, the optimal subsidy on higher education lies above the critical threshold, but is larger under the latter social objective.
Keywords: I25; I28; I31; J17; 330; higher education; mortality risk; insurance; longevity; human capital